Penguatan Kompetensi Guru Non-PLB untuk Penanganan Siswa Berkebutuhan Khusus di Sekolah Dasar Inklusif - Abdul Aziz; Suhirman Suhirman; Rohyana Fitiriani; Husnul Mukti; Dina Apriana (Universitas Hamzanwadi, 2025)
Inclusive education is a strategic approach to fulfilling the right to education for all children, including children with special needs (CSN), within regular school environments. This article discusses a training program designed to enhance teachers' competencies in understanding and fulfilling the role of Special Guidance Teachers (SGTs) in supporting CSN at SDN 4 Pancor and SDN 2 Labuhan Haji, East Lombok Regency. These two public elementary schools are in the early stages of implementing inclusive education. The training was conducted over seven sessions across eight months and covered materials on the concepts of inclusive education, student identification and assessment, the development of individual learning plans, and inclusive teaching strategies. The methods used included lectures, discussions, hands-on practice, and monitoring. Pretest results showed that teachers’ understanding of inclusive education averaged 54%, which increased to 91% in the posttest, indicating a significant improvement. Additionally, teachers' ability to develop simple learning plans and assessments improved from 48% to 88%. Participant satisfaction, measured through questionnaires, increased from 56% to 91%, indicating that the majority of teachers found the training highly relevant and beneficial for inclusive teaching practices. These findings demonstrate that the training program significantly improved teachers' understanding, skills, and readiness to implement inclusive education in primary schools